Risk of SARS-CoV-2 Infection Among Essential Workers in a Community-Based Cohort in the United States - Wei, Chih-Fu; Lan, Fan-Yun; Hsu, Yu-Tien; Lowery, Nina; Dibona, Lauren; Akkeh, Ream; Kales, Stefanos N.; Yang, Justin (Frontiers in Public Health, 2022)
ABSTRACT Objectives: The objective of this paper is to identify risk factors for SARS-CoV-2 infection that are related to occupation type as well as workplace conditions. Identifying such risk factors could have noteworthy policy implications that enhance workplace safety during this SARS-CoV-2 pandemic as well as offer greater health protection to workers themselves. Methods: We conducted a retrospective analysis of visits at a community– based SARS-CoV-2 testing site in the greater Boston area between March 18 and June 19, 2020, for individuals between 14 and 65 years of age. Nasopharyngeal swab specimen, medical review, and self-administered questionnaire were obtained, and SARS-CoV-2 infection was determined with real-time, reverse transcriptase-polymerase chain reaction (RT-PCR). Medical record-verified job classification, customer-facing, and work patterns were extracted from each individual’s response through chart review and validated by medical personnel. The occupational patterns were coded by occupational physicians with pre-specified criteria and were analyzed with logistic regression and inverse probability weighting. Results: Working in healthcare-related jobs was associated with a four-fold increase in risk of SARS-CoV-2 infection (Adjusted OR: 4.00, 95% CI: 1.45-11.02) among the 780 participants included in the analysis. Individuals with customer-facing jobs had a two times risk increase (Adjusted OR: 1.97, 95% CI: 1.12-3.45) in having a positive SARS-CoV-2 RT-PCR assay result compared to participants with non-customer facing positions. Conclusions: In this U.S. community-based population during the initial wave of the pandemic, a significant increase in risk of SARS-CoV-2 infection was observed in those employed in the healthcare sector or with customer-facing positions. Further research is warranted to determine if these correlations continued with the buildup of population immunity together with the attenuation of SARS-CoV-2 virulence.